Species Declines: Examining Patterns of Species Distribution, Abundance, Variability and Conservation Status in Relation to Anthropogenic Activities - Gibbs, Mary Katherine E. (Université d'Ottawa / University of Ottawa, 2012)
Humans are modifying the global landscape at an unprecedented scale and pace. As a result, species are declining and going extinct at an alarming rate. Here, I investigate two main aspects of species’ declines: what factors are contributing to their declines and how effective our conservation efforts have been. I assessed one of the main mechanisms for protecting species by looking at the Endangered Species Act (ESA) in the United States. I examined three separate indicators of species declines for different groups of species: range contractions in Canadian imperilled species, declines in abundance in global amphibian populations and increases in temporal variability in abundance in North American breeding birds. I found that change in recovery status of ESA listed species was only very weakly related to the number of years listed, number of years with a recovery plan, and funding. These tools combined explained very little of the variation in recovery status among species. Either these tools are not very effective in promoting species’ recovery, or species recovery data are so poor that it is impossible to tell whether the tools are effective or not. I examined patterns of species’ declines in three different groups in relation to a number of anthropogenic variables. I found high losses of Canadian imperiled bird, mammal, amphibian and reptile species in regions with high proportions of agricultural land cover. However, losses of imperiled species are significantly more strongly related to the proportion of the region treated with agricultural pesticides. This is consistent with the hypothesis that agricultural pesticide use, or something strongly collinear with it (perhaps intensive agriculture more generally), has contributed significantly to the decline of imperiled species in Canada. Global increases in UV radiation do not appear to be a major cause of amphibian population declines. At individual sites, temporal changes in amphibian abundance are not predictably related to changes in UV intensity. Variability in species’ abundance of North American breeding birds, after accounting for mean abundance, is not systematically higher in areas of high human-dominated land cover or climate change. Rather, it appears that areas with a high proportion of human-dominated cover come to have a higher proportion of highly abundant, and thus more variable, species.
Keywords: conservation; species declines; habitat loss; climate change; global amphibian declines; pesticides; Endangered Species Act